NCMP-11. THE CANCER AND COGNITION CLINIC AT WAKE FOREST BAPTIST HOSPITAL: SATISFYING AN UNMET NEED. (11th November 2019) - Cummings, Tiffany; Giles, Abigail; Liberatore, Mary; Laxton, Adrian; Carter, Annette; Tatter, Stephen; Chan, Michael; Lesser, Glenn; Strowd, Roy; Cramer, Christina
Abstract: Preservation of cognitive functioning is a top priority for brain tumor patients but is often not addressed in a systematic manner. To address this unmet need, we established a virtual neurocognitive clinic within our brain tumor center. The aim was to incorporate standardized neuropsychological examinations into routine care. To make neuropsychological testing achievable for patients with primary brain tumors, we developed a one-hour battery to measure core cognitive functions. We established a process where patients are offered cognitive testing at initial consult by neuro-oncology or radiation oncology. To reduce the burden of an extra appointment, patients are seen by neuropsychology in the Cancer Center (as opposed to the main hospital). Appointments are coordinated on the same day as other essential visits. Results are reviewed in multidisciplinary tumor boards. When possible, patients are seen for serial cognitive assessments at 3, 6 and 12 months after RT treatment. Providers in neuro-oncology, neurosurgery, and radiation oncology were encouraged to refer survivors to neuropsychology. After the clinic launch in 2017, 143 brain tumor patients were referred to neuropsychology. Prior to the clinic launch, 22 referrals were made over a comparable timeframe. Cognitive deficits were identified in most patients. After testing, patients received education on the brain-function relationship pertaining to their deficits. The patients' referring provider received a full report containing recommendations for interventions based on testing outcomes 11 of the 38 patients who underwent pre-treatment assessments underwent testing 6 months post-RT. With the recent addition of a dedicated clinical coordinator, the rate of successful post-treatment cognitive evaluation is increasing. The cognitive, emotional, behavioral, and psychosocial impact of a brain tumor can be difficult to categorize and treat without formal evaluation. Integrating neuropsychological examination into routine care has resulted in a massive increase in the number of brain tumor patients getting a neuropsychologic assessment.